2019
DOI: 10.3389/fimmu.2019.01500
|View full text |Cite
|
Sign up to set email alerts
|

Human Antimicrobial RNases Inhibit Intracellular Bacterial Growth and Induce Autophagy in Mycobacteria-Infected Macrophages

Abstract: The development of novel treatment against tuberculosis is a priority global health challenge. Antimicrobial proteins and peptides offer a multifaceted mechanism suitable to fight bacterial resistance. Within the RNaseA superfamily there is a group of highly cationic proteins secreted by innate immune cells with anti-infective and immune-regulatory properties. In this work, we have tested the human canonical members of the RNase family using a spot-culture growth inhibition assay based mycobacteria-infected ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 84 publications
6
52
1
Order By: Relevance
“…Previously, our research group designed and explored the mechanism of action of a novel hybrid ribonuclease RNase 3/1, towards Gram-negative microorganisms [15]. Additionally, numerous studies have demonstrated the effective activity of the human RNase 3 to inhibit the intracellular growth of several microorganisms, including Mycobacterium [16] and even the proliferation of biofilm structures of P. aeruginosa [12]. In parallel, we have developed a nanoplatform based on modified magnetite nanoparticles (MNPs) for the efficient immobilization of antimicrobial and cell-penetrating molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, our research group designed and explored the mechanism of action of a novel hybrid ribonuclease RNase 3/1, towards Gram-negative microorganisms [15]. Additionally, numerous studies have demonstrated the effective activity of the human RNase 3 to inhibit the intracellular growth of several microorganisms, including Mycobacterium [16] and even the proliferation of biofilm structures of P. aeruginosa [12]. In parallel, we have developed a nanoplatform based on modified magnetite nanoparticles (MNPs) for the efficient immobilization of antimicrobial and cell-penetrating molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Although the catalytic activity of the protein was reduced, the antibacterial activity was maintained and increased After immobilization on MNP. Recent studies have demonstrated that indeed, the antimicrobial and catalytic activities appear unrelated [16,86]. Finally, it should be noted that the obtained nanobioconjugates were prepared at a single RNases:MNPs ratio, as detailed in the Materials and Methods section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, RNase3 internalization is observed in treated yeast cells and protozoa [8,13]. Besides, RNase3 can enter the macrophage and eradicate the intracellular dwelling bacteria [14]. On the other hand, the protein antiviral activity on single stranded RNA viruses has been directly correlated to its ribonucleolytic action [9].…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial properties of this variant are carried out by inducing bacteria agglutination (66). Furthermore, RNase 6, as well as RNase 3, is highly effective against Mycobacterium aurum by inducing an autophagy process in the infected macrophages (67).…”
Section: Introductionmentioning
confidence: 99%